Children's Ideas About What It Means 'to Get Better' at History: A View from the UK. Issue 2 (1st October 2009) - Haydn, Terry; Harris, Richard
The past three decades have seen radical changes in history educators', policymakers' and educationalists' ideas about what it means 'to get better' in history brought about a much more clearly defined framework for progression in the subject. The introduction of formal (and quite complex) models for measuring pupils' progress in history, and changing and contested ideas about progression in history as a school subject occasioned vigorous debate, both between politicians, historians and history teacher educators, and between teacher educators themselves. at history, and the extent of their understanding of the models of progression, which have been developed in recent years. The research asked pupils to explain in their own words what they thought it meant 'to get better at history'. The outcomes revealed that many pupils had very little understanding of the models for progression for history which have been put in place in UK schools, and quite vague and inchoate ideas about what it means to make progress in history. Only a minority of pupils, in some of the schools involved, were able to explain progression in specifications, and as expounded in adult discourse about history education. It is possible that many teachers have perhaps made assumptions about the extent to which pupils understand what they have to do to make progress in history, and that more time and thought might be invested in this aspect of history education in order to improve pupil motivation and attainment in history.